Othello / William Shakespeare - Muir Kenneth (Penguin Books, 1982)
Introduction, Further Reading, Othello, Commentary, An Account of the Text, The Songs.
Introduction, Further Reading, Othello, Commentary, An Account of the Text, The Songs.